PENGUJIAN PARAMETER SPESIFIK, NON SPESIFIK, AKTIVITAS ANTIOKSIDAN PADA SIMPLISIA BUAH JERUK NIPIS (Citrus aurantiifolia (Christm) Swingle) - Elsa Marliana; Tiara Briliana Amadar Nikazato (Politeknik META Industri Cikarang, 2025)
Plants that are often used to make herbal medicine, especially to strengthen the immune system, include herbs containing red ginger, lime, and cinnamon. Based on the herbal medicine, there are ingredients that are often added for freshness, namely lime. Although fresh plants can be used, these basic ingredients can also rot quickly if not used immediately. Meta Industri Cikarang Polytechnic has superior products in the field of herbal medicine, one of the ingredients added to the potion is lime. In order to develop fresh herbal products into herbal medicines in dry form, it is necessary to dry the herbal ingredients according to the quality requirements of the herbal medicine. The research method used is experimental, the lime fruit sample came from the Cikarang Traditional Market, Bekasi. The process of making herbal medicine is carried out by drying using a food dehydrator at a temperature of 60 ℃ for 48 hours, producing dry herbal medicine that is orange-brown in color, has a distinctive lime odor, and a slightly bitter sour taste. The sample is in the form of slices 3.7 cm long and 3.2 cm wide, with the same colored powder that feels slightly sticky. Identification fragments include pericarp, vascular bundles with ladder thickening, covering hairs, endosperm, endocarp parenchyma, prism calcium oxalate crystals, and oil drops. Chemical identification shows the content of alkaloids, flavonoids, terpenoids, and saponins. The drying shrinkage value is 8.3%; ALT 5.5 ???? 102 ???????????? / ????; AKK is <1 ???? 101 ???????????? / ????. Antioxidant activity test using the DPPH method obtained IC50 87.72 µg / ml. Based on the test results, it shows that lime fruit simplicia meets the quality requirements of simplicia and has strong antioxidant activity